EFEKTIFITAS IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS ONLINE DI SDN CIKUYA III - Wahyu Ningsih; Siti Napsah; Naimatun Nafilah; Cindy Nurhaliza (el-Moona: Jurnal Ilmu Pendidikan Islam, 2021)
This research is motivated by the existence of full online learning (100% online) As a result of Covid-19, news circulated that online learning is less effective, because there has been no maximum preparation in terms of regulation, implementers on the ground, and also students, and as an infrastructure to support online learning, therefore researchers have the desire to test the level of effectiveness of learning, because there should be no learning content lost in the midst of this pandemic. This research there are several obstacles experienced by teacher students and parents of students, namely the mastery of technology is still lacking, constrained by internet quotas, and not all teachers have the same digital literacy not all teachers and students have minimal devices that can be used, so online learning is difficult to do, the quality of connections and the availability of data packages are still limited. Therefore, researchers have the desire to test the level of learning effectiveness, because there should be no learning content lost in the midst of this pandemic. The research method used is the exploratory survey method and the approach using qualitative methods used to get information on covid 19 constraints